Religiosity and Greek nurses’ death attitude - Malliarou, Maria; Zyga, Sofia; Constantinidis, Theodoros; Sarafis, Pavlos (My University, 2014)
Background: Most religions offer a framework to answer existential questions concerning death and dying. The aim of this study was to find the association between Greek nurses’ religious attitudes and death attitudes. Methods: A cross-sectional analytical study took place in two General Greek hospitals. 102 Registered nurses and nurses’ aides answered an anonymous self-administered questionnaire about their religiosity and their attitude death (RR=64,3%). Analysis of data was performed with statistical methods of descriptive and inferential statistics. SPSS (version 19) was used for the analysis. Findings: The majority of the sample was orthodox. Nurses who answered that religiosity doesn’t affect their attitude towards death were found to have greater fear of death with p=0.000 and avoid death more (p=0.012). Nurses who admit that religiosity affects their attitude towards death the most, they were found to accept death more in relation to those who say that their religiosity doesn’t affect their attitude towards end-stage patients care (p=0.000). Discussion: Religiosity is a factor that correlates statistically significant with Greek nurses attitude towards death.
Keywords: Death; Greek nurses; Religion